RESEARCH VARIANTS OF AIR ACCUMULATING POWER STATION CONSTRUCTION AND THEIR SUBSTANTIATIONS - Mokin, Boris; Chepurnyj, Marko; Mokin, Oleksandr (Scientific Works of Vinnytsia National Technical University, 2011)
There had been offered variants of construction of the small air heat-sink power station suitable for research of processes in it. The design procedure of key parameters of this research station is presented.